Research Progress on the Mechanism of Stone Expulsion with Traditional Chinese Medicine: From Traditional Experience to Modern Pharmacology - Yuan, Chuhan; Zhang, Yujun (Journal of Contemporary Medical Practice, 2025)
Traditional Chinese medicine (TCM) has a long history of application and significant clinical efficacy in the treatment of urinary tract stones, demonstrating its multi-mechanism and multi-target therapeutic advantages. This article systematically reviews the pharmacological effects and current clinical application of TCM lithostomy. It highlights numerous challenges, including the complexity of active ingredients, unclear mechanisms of action, a lack of high-quality clinical research, lagging standardization of formulations, and the modern translation of syndrome differentiation and treatment. To address these challenges, it is proposed that future research should focus on the isolation of active ingredients and target identification, the application of multi-omics technologies in mechanism analysis, the development of novel formulations, the establishment of standardized clinical pathways, and the optimization of synergistic treatment models combining traditional Chinese and Western medicine. As a bridge connecting traditional and modern medicine, TCM lithostomy has broad development potential. Promoting its development towards precision, standardization, and internationalization will provide more scientific and efficient solutions for the comprehensive treatment of urinary tract stones.